2015
DOI: 10.1093/infdis/jiv440
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniaeFimK Promotes Virulence in Murine Pneumonia

Abstract: Klebsiella pneumoniae, a chief cause of nosocomial pneumonia, is a versatile and commonly multidrug-resistant human pathogen for which further insight into pathogenesis is needed. We show that the pilus regulatory gene fimK promotes the virulence of K. pneumoniae strain TOP52 in murine pneumonia. This contrasts with the attenuating effect of fimK on urinary tract virulence, illustrating that a single factor may exert opposing effects on pathogenesis in distinct host niches. Loss of fimK in TOP52 pneumonia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
1
35
0
1
Order By: Relevance
“…K. pneumoniae also carries a gene not carried by E. coli, fimK, whose exact function is unknown. One theory is that FimK is involved in type 1 fimbrial regulation, due to the loss of type 1 fimbria expression upon deletion of fimK (116,283). K. pneumoniae type 1 fimbriae bind D-mannosylated glycoproteins, and therefore, binding by type 1 fimbriae is frequently termed "mannose-sensitive" binding (284,285).…”
Section: Type 1 and 3 Fimbriaementioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae also carries a gene not carried by E. coli, fimK, whose exact function is unknown. One theory is that FimK is involved in type 1 fimbrial regulation, due to the loss of type 1 fimbria expression upon deletion of fimK (116,283). K. pneumoniae type 1 fimbriae bind D-mannosylated glycoproteins, and therefore, binding by type 1 fimbriae is frequently termed "mannose-sensitive" binding (284,285).…”
Section: Type 1 and 3 Fimbriaementioning
confidence: 99%
“…This suggests that even a small amount of type 1 fimbria expression may be detrimental for survival in these sites. Along these lines, experiments in a mouse model found that a K. pneumoniae strain lacking fimK, which resulted in the overexpression of type 1 fimbriae, was attenuated during lung infection (283). However, it should be noted that this phenotype could also be due to the associated decrease in capsule production that occurs in a fimK mutant (283).…”
Section: Figmentioning
confidence: 99%
“…Biofilms formation were assayed using the standard crystal violet quantification assay described by O'Toole and associates [88]. Serum-killing assay was performed based on the method described by Rosen and associates [89]. G. mellonella infection assay was conducted as described by McLaughlin and associates [90].…”
Section: Klebsiella Isolated Strainsmentioning
confidence: 99%
“…MICs of these pathogens were determined according to the CLSI M07-A8 2011 guidelines. The serum-killing assay was performed based on the method described by David and associates [32].…”
Section: Antibiotic Susceptibility Test and Serum Killing Resistance mentioning
confidence: 99%